Ethical and cultural value of the Earth sciences. Interview with Prof. Giulio Giorello - Silvia Peppoloni (Annals of Geophysics, 2012)
Prof. Giulio Giorello is amongst the most prominent philosophers of science in Italy and in the world. He is currently Professor of the Philosophy of Science at the University of Milan, Director of the Series ‘Science and Ideas’ (Raffaele Cortina Books Editor), and Literary Journalist of the cultural pages of the Corriere della Sera, one of the most important of the Italian newspapers. In this keynote presentation, in interview form, he talks about the value that the Earth sciences have had through history, framing this group of disciplines in ethical and epistemological terms, and highlighting some important elements that have to be considered in geological activities.